2020
DOI: 10.1186/s12913-020-05905-z
|View full text |Cite
|
Sign up to set email alerts
|

The micropolitics of implementation; a qualitative study exploring the impact of power, authority, and influence when implementing change in healthcare teams

Abstract: Background Healthcare organisations are complex social entities, comprising of multiple stakeholders with differing priorities, roles, and expectations about how care should be delivered. To reach agreement among these diverse interest groups and achieve safe, cost-effective patient care, healthcare staff must navigate the micropolitical context of the health service. Micropolitics in this study refers to the use of power, authority, and influence to affect team goals, vision, and decision-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 72 publications
3
58
0
Order By: Relevance
“…As researchers start to grapple with the intersection of implementation science and health equity [ 46 ], carefully identifying who is suggesting the modifications may be an important aspect of tracking the co-creation of implementation strategies [ 21 24 ]. Identifying sources of power in the implementation process [ 47 ], and incorporating the voices of those in the community, will be important for the field as we move toward equitable practice in our science.…”
Section: Components Of the Frame-ismentioning
confidence: 99%
“…As researchers start to grapple with the intersection of implementation science and health equity [ 46 ], carefully identifying who is suggesting the modifications may be an important aspect of tracking the co-creation of implementation strategies [ 21 24 ]. Identifying sources of power in the implementation process [ 47 ], and incorporating the voices of those in the community, will be important for the field as we move toward equitable practice in our science.…”
Section: Components Of the Frame-ismentioning
confidence: 99%
“…Recent reviews of the literature found the involvement of service users/patients still at low and often tokenistic levels 16,26 . Apparent gaps in scientific rigour, tensions and hierarchical power differences between those involved in the process, coupled with a focus on short‐term outcomes, raise questions regarding the use of co‐design 16,34 . Few works provide any evidence or guidance on supporting the involvement of health‐care staff who may have a diverse range of needs to support their full participation 27 .…”
Section: Unintended Consequences From Co‐designmentioning
confidence: 99%
“… 16 , 26 Apparent gaps in scientific rigour, tensions and hierarchical power differences between those involved in the process, coupled with a focus on short‐term outcomes, raise questions regarding the use of co‐design. 16 , 34 Few works provide any evidence or guidance on supporting the involvement of health‐care staff who may have a diverse range of needs to support their full participation. 27 There are strong critiques on the use of narrow approaches that lack the involvement of priority populations, having co‐design approaches set before a project commences, and the process being managed by health‐care staff.…”
Section: Unintended Consequences From Co‐designmentioning
confidence: 99%
“…Successful implementation needs appropriate funding, planning and strategies that address the complexity and micro-politics embedded within all health care systems. Implementation strategies need to support individual practitioners, managers, and understand the context as well as receive strong organisational support and patronage which is in uential to normalising a new practice among staff 23 . An evidence informed and context speci c implementation strategy is essential to sustained, reliable and high uptake 16,24 .…”
Section: Discussionmentioning
confidence: 99%